Acupuncture and NSAIDs Reduce Neurogenic-Pain and Matrix Degradation Biomarkers in a Rat Model of Osteoarthritis - Mayang Wulandari; Achmad Jaelani; Fitria Novitasari; Wahyudha Ngatiril Lady (GLOBAL HEALTH SCIENCE GROUP, 2026)
Osteoarthritis (OA) is a degenerative joint disease characterized by neurogenic pain and cartilage degradation, with serum biomarkers (SP, NGF, COMP, and MMP-13) serving as indicators of pain signaling, tissue damage, and treatment effects. This study aimed to compare the effects of acupuncture and a nonsteroidal anti-inflammatory drug (NSAID) on neurogenic pain and cartilage degradation biomarkers in a rat OA model. A randomized post-test-only experimental study was conducted using 32 male Wistar rats selected by purposive sampling and randomly allocated into four groups (n=8/group): healthy control, OA control, OA+acupuncture, and OA+NSAID. OA was induced by intra-articular monosodium iodoacetate. Acupuncture was administered at ST35, SP9, and GB34 for 10 sessions, while the NSAID group received oral meloxicam. Serum biomarkers were measured by ELISA and analyzed using one-way ANOVA with Tukey’s HSD (p<0.05). Results: Significant differences were observed among all groups for each biomarker (p<0.001) with large effect sizes. Biomarker levels followed the pattern A < M ≈ S < K. Both treatment groups showed significant reductions compared to OA controls, with no significant difference between acupuncture and NSAID. Acupuncture and NSAID treatments produced comparable improvements in OA-related biomarkers, supporting multimodal therapeutic approaches for OA.